Đặc điểm nước dưới đất trong vùng cát ven biển miền Trung Việt Nam và định hướng khai thác sử dụng - Tặng, Nguyễn Xuân; Hạnh, Tạ Văn (Vietnam Journal of Earth Sciences, 2012)
summary Characteristic of groundwater in coastal sand area of Central Vietnam and orientation for exploitation and utilization Groundwater in the Quaternary sediment of coastal sand area of central Vietnam is fresh water only on spot that can be exploited for living and socioeconomic development in the area. However, reserve of fresh groundwater is very limited and easily to be polluted by pollutants and sea water. This paper refers to the potential for fresh groundwater in the coastal sand area of central Vietnam and the state of exploitation, utilization, as well as problems related to the orientation for rational exploitation and utilization of fresh groundwater for living and socioeconomic development in the area.